Portrait Of Project Based MKWK Learning As An Effort To Build Superior Morality In Students - Muhlis Fajar Wicaksana; Akhmad Rosyid; Toni Harsan; Siti Fatimah (Jurnal Ilmu Sosial Mamangan, 2024)
The moral education among university students has become a focus of attention in facing moral decadence in this modern era. Superior morality is not only an aspiration but also an essential foundation in shaping students' characters with integrity and high competitiveness. Therefore, this research aims to provide an overview through project-based Moral, Character, and Citizenship Education (MKWK) in efforts to combat moral decadence among students. This research uses a qualitative approach with a Participatory Action Research design to identify the role and benefits of this MKWK learning. Data collection techniques are conducted through observation, interviews, and analysis of documents related to the implementation of project-based MKWK learning. The sampling technique for this research refers to random sampling. The data analysis technique for this research uses triangulation data analysis, which includes data from observations, interviews, and document analysis. The results of the research show that project-based MKWK learning can be an effective tool in building superior morality in students. The project-based learning process unleashes the creative and collaborative potential of students in solving real challenges related to social, economic, or environmental issues. This approach also helps students develop crucial problem-solving, communication, and leadership skills in building meaningful morality. This research significantly contributes to the development of moral education in higher education by proposing a model of project-based MKWK learning. This model is expected to be widely integrated into higher education curricula to shape superior morality in students and have a positive impact on society. However, the research has limitations in terms of the number of participants and the limited duration of the study. Therefore, further research is recommended with a larger sample size and longer duration to strengthen the findings and generalize the results.